Actividad antioxidante en guanábana (Annona muricata l.) : una revisión bibliográfica - Correa Gordillo, J; Ortíz, Darwin; Larrahondo, J; Sánchez Mejía, M.; Pachón, Helena (2012)
An antioxidant is a compound capable of inhibiting molecular oxidation and therefore of protecting biological molecules from reactive oxygen species or free radicals. Antioxidants can be synthesized by the body or obtained from a diet containing fruit, such as soursop. The aim of this project was to review the literature on antioxidant activity of the soursop and compounds that might be responsible for this activity. From the analysis of fourteen studies, we found that in most cases soursop did not contain high activity or concentration of antioxidants in fresh or frozen pulp, in comparison with highly consumed fruits in Colombia. The leaves, as well as the juice and wine from the plant, do not contain high activity or concentration of antioxidants. In-depth characterization of antioxidant activity and compounds in soursop is lacking; additional studies are required to identify the mechanisms of action of the compounds present in the whole fruit (peel and seed) for different varieties of this tropical fruit.